2021
DOI: 10.3389/fonc.2021.759903
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Oncological Efficacy Between Intraoperative Radiotherapy With Whole-Breast Irradiation for Early Breast Cancer: A Meta-Analysis

Abstract: BackgroundIntraoperative radiotherapy (IORT) and whole-breast irradiation (WBI) are both effective radiotherapeutic interventions for early breast cancer patients undergoing breast-conserving surgery; however, an issue on whether which one can entail the better prognosis is still controversial. Our study aimed to investigate the 5-year oncological efficacy of the IORT cohort and the WBI cohort, respectively, and compare the oncological efficacy between the cohorts.Materials and MethodsWe conducted a computeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…After five years of follow-up, local recurrence was 3.96% vs. 1.05%. However, after median nine-year long-term follow-up, the rates of local recurrence-free survival, mastectomy-free survival, distant disease-free survival, and overall survival were the same IORT: intraoperative radiotherapy; PBRT: partial breast radiation therapy; EBRT: external-beam radiation therapy; %: percentage Table 5 summarizes the results from meta-analysis or data mining analysis [42][43][44][45]. The data establish the safety and equivalency of outcomes between IORT-based PBRT and WBRT outside of the randomized clinical trial settings.…”
Section: Targit-related Studies Using Intraoperative Radiotherapy-bas...mentioning
confidence: 99%
See 1 more Smart Citation
“…After five years of follow-up, local recurrence was 3.96% vs. 1.05%. However, after median nine-year long-term follow-up, the rates of local recurrence-free survival, mastectomy-free survival, distant disease-free survival, and overall survival were the same IORT: intraoperative radiotherapy; PBRT: partial breast radiation therapy; EBRT: external-beam radiation therapy; %: percentage Table 5 summarizes the results from meta-analysis or data mining analysis [42][43][44][45]. The data establish the safety and equivalency of outcomes between IORT-based PBRT and WBRT outside of the randomized clinical trial settings.…”
Section: Targit-related Studies Using Intraoperative Radiotherapy-bas...mentioning
confidence: 99%
“…It segregated them into two groups based on whether they received IORT or EBRT after surgery. The results indicate that there is no difference between cancer-specific survival and overall survival 3 Yin Mi used a propensity score matching based on the SEER database[44], published in 2022, to investigate the overall survival and BCS outcomes of IORT compared to no RT in low-risk EBC. The study enrolled approximately 20,000 patients diagnosed with earlystage breast cancer between 2010 and 2019.…”
mentioning
confidence: 99%
“…While several studies and meta‐analyses have shown promising results of PBI in suitable low‐risk breast cancer patients, 17,18 two recently published cohort studies and a randomized clinical trial reported higher than expected rates of IBTR in patients treated with electron beam IORT 19–21 . No effects were reported on distant metastasis rates, nor on cancer‐specific or overall survival 20,22,23 …”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] No effects were reported on distant metastasis rates, nor on cancer-specific or overall survival. 20,22,23 The aim of this study was to report our data on a large series of IBTR after electron beam IORT and to identify possible risk factors for IBTR in patients with suitable low-risk breast cancer. 24 2 | MATERIALS AND METHODS…”
Section: Introductionmentioning
confidence: 99%